Chaetomitrium Elmeri - Monica Suleiman; Hiroyuki Akiyama (Museum of Nature and Human Activities, 2014)
(1) Branches are rigid, sub-erect, tumid and obtuse; (2) branch leaves are imbricate-patent, lingulate, deeply concave, with obtuse or rounded apices; (3) leaf margins are strongly incurved and denticulate with simple teeth; (4) costae are strong; (5) lamina cells are linear and prorulate; upper half of the adaxial side have numerous large tuberculae, each up to 24 μm in diameter; (6) setae are 22 - 25 mm long, papillose above and smooth below; (7) capsules are sub-erect and smooth; (8) calyptrae are cucullate, densely hispid over the surface but naked at the base.